2021
DOI: 10.3390/environments8060055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Forest Management and Sylvicultural Treatments on Abundance of Snags and Tree Cavities in Mountain Mixed Beech Forests

Abstract: In this study the influence of forest management on the characteristics of snags and tree cavities in the Hyrcanian forests of Iran was investigated. In particular, the effect of two sylvicultural treatments (shelter wood and single-tree selection) was assessed in comparison to protected stands. The abundance, diameter, height, and degree of decay of snag species, and the characteristics of birds excavated and natural cavities (number and height from the ground level) were measured by systematic plots in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…The results of this study showed that the frequency and volume of live trees were significantly lower in the harvested stands (Sh and Sc) than the protected stands (Pr), especially the frequency of large diameter trees. Other studies have also concluded that the frequency and volume of trees in the harvested stands were lower than in the protected stands [16,52,[58][59][60][61][62][63].…”
Section: Live Treesmentioning
confidence: 94%
See 4 more Smart Citations
“…The results of this study showed that the frequency and volume of live trees were significantly lower in the harvested stands (Sh and Sc) than the protected stands (Pr), especially the frequency of large diameter trees. Other studies have also concluded that the frequency and volume of trees in the harvested stands were lower than in the protected stands [16,52,[58][59][60][61][62][63].…”
Section: Live Treesmentioning
confidence: 94%
“…The Hyrcanian forests have been managed by different silvicultural treatments [16,47,57], as follows: shelterwood cutting from 1970 to 2000 (Sh stands), selection cutting from 2000 to 2014, and restricted cutting to damaged and fallen trees from 2016 to the present (Sc stands). The main natural disturbance in the Hyrcanian mountain forests in northern Iran is the wind that blows over and damages some trees every year.…”
Section: Live Treesmentioning
confidence: 99%
See 3 more Smart Citations